Studi Fenomenologi Konsep Bisnis Berkelanjutan dalam Konteks Pegiat UMKM - Diantoro, Eman; Suheri, Suheri; Arianto, Bambang (Universitas Proklamasi 45, 2024)
This study elaborates on sustainable business in the context of Micro, Small, and Medium Enterprises (MSMEs). MSMEs play an important role in strengthening the national economy, so a concept of business sustainability is needed when facing economic, social, and environmental challenges. This study involved three subjects who are MSME activists who are concerned about environmental and social aspects. This study uses a phenomenological study approach with the Interpretative Phenomenological Analysis method. Data were obtained through in-depth interviews and observations with categories based on statements from research subjects who are MSME activists in the Serang Regency. The research subjects stated that MSME activists have diverse understandings of sustainable business, which include aspects of resource efficiency, and social and environmental responsibility. Sustainable practices arise more from practical needs, such as cost savings and increasing competitiveness, compared to more strategic environmental or social motivations. This study found that despite facing many challenges, MSME activists already understand the concept of sustainable business can have a positive impact on the development of MSME businesses in an increasingly competitive era.